Human rights as the object of comparative-historical legal researches in the works of Ivanyshev M.D. - Kudin, Serhii Volodymyrovych (Класичний приватний університет, 2018)
У статті досліджується змістовний характер проведеного М.Д. Іванишевим історичного порівняння розвитку прав людини у різних народів. З`ясовано, що ідея особистості у працях вченого тісно перепліталась з контрастним історичним порівнянням права наднаціональних слов`янських та німецьких етноспільнот з врахуванням культурних властивостей народів. Встановлено, що розвиток прав людини уявлявся ним як певний повільний та поетапний еволюційний процес. З`ясовано, що М.Д. Іванишев досліджував відмінності деяких інститутів приватного скандинавського та богемського права у дохристиянський період. На підставі порівняння правових звичаїв цих народів він визначив, що правовий статус особи за нормами богемського права мав більш прогресивні риси, ніж за нормами скандинавського права.

The article investigates the substantive nature of our historical comparison of human rights in different nations by Ivanishev M. D. It was found that the idea of the individual in the works of the scientist is closely intertwined with contrasting historical comparison of supranational law of Slavic and German ethnic communities with cultural characteristics of nations. Found that the development of human rights seemed to him as a definite, slow and gradual evolutionary process. It was found that Ivanishev M. D. investigated the differences of some institutions of Private Scandinavian and Bohemian law in the pre-Christian period. Comparing the legal customs of those nations, he found that the legal status of the individual provisions of the Bohemian law had more advanced features than the norms of the Scandinavian law.
Keywords: human rights; comparative-historical researched; historical legal school; Slavic law; scientific works of Ivanyshev M.D; права людини; порівняльно-історичні дослідження; історична школа права; слов`янське право; наукова творчість М.Д. Іванишева.